Association of Contraceptive Knowledge, Sexual Double Standard and Contraceptive Self-Efficacy among Unmarried Women in Their 30s and 40s - Kye ha Kim; Euna Cho (Korean Society of Women Health Nursing, 2019)
PURPOSE: To determine association of contraceptive knowledge, sexual double standard, and contraceptive self-efficacy among unmarried women in their 30s and 40s. METHODS: With a survey design, data were collected from 119 unmarried women in their 30s and 40s in G city of Korea from September 2017 to March 2018. Data were analyzed by descriptive statistics, independent t-test, one-way ANOVA, Scheffé test, Pearson's correlation coefficients, and stepwise multiple regression. RESULTS: Contraceptive knowledge, sexual double standard, and contraceptive self-efficacy scores of participants were 8.97±2.22, 18.54±5.57, and 45.84 ± 6.90, respectively. Contraceptive self-efficacy was negatively correlated with sexual double standard. Factors influencing contraceptive self-efficacy were sexual double standard (β =−.26, p=.003), existence of boyfriend (β=.25, p=.004), and contraceptive education need for adults (β=.17, p=.044). They explained 19% of contraceptive self-efficacy of participants. CONCLUSION: To increase contraceptive self-efficacy of unmarried women in their 30s and 40s, lowering sexual double standard and developing customized contraceptive education according to age and knowledge level are needed. Research on factors related to contraceptive self-efficacy of unmarried women in their 30s and 40s from various regions are also needed in the future.